Development of Visual Media Tree Chart with the theme of Archipelago Culinary to Improve the Ability to Write Descriptive Text of Grade VII SMP Pondok Pesantren Al-Huda Grogol - Lestari, Nurul Dwi; Azizah, Anis Nur; Halimah, Halimah (UIR Press, 2024)
In effective and efficient learning, supporting tools are needed to achieve learning goals. Supporting tools in the form of visual media can be used as a support to make it easier for teachers and students in teaching and learning activities. This research discusses the development of visual tree chart learning media containing Indonesian culinary delights to improve the ability to write descriptive text for class VII middle school students. This media aims to facilitate Indonesian language learning by introducing and describing Indonesian culinary delights through visual tree chart media. The development approach used is Research and Development (R&D), with a 4-D development model, which includes the stages of definition, design, development and deployment. The research subjects involved media experts, material experts, teachers and class VII students at the Al-Huda Grogol Islamic Boarding School Middle School. Data collection methods involve interviews, observations, and tests. The research results show that media tree charts with an Indonesian culinary theme are considered appropriate by media experts and material experts. Field trials with students resulted in an average assessment score of 77.83%, indicating that this media is suitable for use in learning.